2015
DOI: 10.4137/cgm.s21215
|View full text |Cite
|
Sign up to set email alerts
|

Use of Animal Models in Understanding Cancer-induced Bone Pain

Abstract: Many common cancers have a propensity to metastasize to bone. Although malignancies often go undetected in their native tissues, bone metastases produce excruciating pain that severely compromises patient quality of life. Cancer-induced bone pain (CIBP) is poorly managed with existing medications, and its multifaceted etiology remains to be fully elucidated. Novel analgesic targets arise as more is learned about this complex and distinct pain state. Over the past two decades, multiple animal models have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 171 publications
(285 reference statements)
0
47
0
Order By: Relevance
“…[12][13][14]19 However, to the best of our knowledge, this is the first study showing the involvement of TRPA1 in a model of cancer pain. In addition, whereas a role for oxidative stress in models of cancer pain has been previously proposed, 35,39,48 this is the first paper showing that increased oxidative stress sustains cancer pain via its ability to target TRPA1 in nociceptors.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…[12][13][14]19 However, to the best of our knowledge, this is the first study showing the involvement of TRPA1 in a model of cancer pain. In addition, whereas a role for oxidative stress in models of cancer pain has been previously proposed, 35,39,48 this is the first paper showing that increased oxidative stress sustains cancer pain via its ability to target TRPA1 in nociceptors.…”
Section: Discussionmentioning
confidence: 89%
“…Different animal models have recently been proposed for reproducing metastatic cancer‐related pain, including tumor cells injection in the bone or the plantar pad . Previous studies showed that subcutaneous injection in the hind paw of B16‐F10 melanoma cells induces mechanical and cold allodynia that can be assessed 14 days after cells inoculation .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,63 Although the bone is innervated by both sympathetic and nociceptive nerve fibers, many tumors of the bone in humans lack detectable nerve fibers within the tumor and adjacent peripheral bone. 31,42 Contributors to nociceptive signaling associated with CIBP include an acidic tumor environment and the secretion of growth factors, cytokines, and chemokines from the tumor and tumor-associated cells, as well as enhanced nerve sprouting in the local environment.…”
Section: Introductionmentioning
confidence: 99%
“…About 75–90% of patients with metastatic or advanced-stage cancer will suffer metastatic cancer-induced bone pain (CIBP), and the severity of CIBP is closely correlated with the extent of bone destruction [13]. CIBP is commonly induced by primary bone cancer or secondary bone metastasis from other malignancies, such as breast, prostate, and lung cancer, which may produce excruciating bone pain [46]. Generally, the primary treatment of CIBP is utilization of opioids and other adjuvants, such as morphine, nonsteroidal anti-inflammatory drugs, and cannabinoids [7].…”
Section: Introductionmentioning
confidence: 99%